Neural Transplants From Human Induced Pluripotent Stem Cells Rescue the Pathology and Behavioral Defects in a Rodent Model of Huntington’s Disease - Yongwoo Yoon; Hyun Sook Kim; Chang Pyo Hong; Endan Li; Iksoo Jeon; Hyun Jung Park; Nayeon Lee; Zhong Pei; Jihwan Song; Jihwan Song (Frontiers in Neuroscience, 2020)
Huntington’s disease (HD) is a devastating, autosomal-dominant inheritance disorder with the progressive loss of medium spiny neurons (MSNs) and corticostriatal connections in the brain. Cell replacement therapy has been proposed as a potential therapeutic strategy to treat HD. Among various types of stem cells, human-induced pluripotent stem cells (iPSCs) have received special attention to develop disease modeling and cell therapy for HD. In the present study, the therapeutic effects of neural precursor cells (NPCs) derived from a human iPSC line (1231A3-NPCs) were investigated in the quinolinic acid (QA)-lesioned rat model of HD. 1231A3-NPCs were transplanted into the ipsilateral striatum 1 week after QA lesioning, and the transplanted animals showed significant behavioral improvements for up to 12 weeks based on the staircase, rotarod, stepping, apomorphine-induced rotation, and cylinder tests. Transplanted 1231A3-NPCs also partially replaced the lost neurons, enhanced endogenous neurogenesis, reduced inflammatory responses, and reconstituted the damaged neuronal connections. Taken together, these results strongly indicate that NPCs derived from iPSCs can potentially be useful to treat HD in the future.